2008
DOI: 10.1111/j.1747-0285.2007.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Trishomocubane Amino Acid as a β‐turn scaffold

Abstract: The synthesis and X-ray structure of two diasteriomeric heptapeptides [Ac-Ala-Ala-Ala-(R/S)-Cage-Ala-Ala-Ala-NH2] with a trishomocubane amino acid as a beta-turn scaffold are reported. The amino acid was synthesized as a racemate and two diastereomeric peptides were obtained. The two peptides were separated by preparative high-pressure liquid chromatography and crystals suitable for X-ray analysis were grown for both diasteriomeric peptides. In general, both the peptides satisfy the criteria for beta-turn conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 57 publications
(84 reference statements)
0
15
0
Order By: Relevance
“…1 Criteria used in the identification of γand β-turn characteristics. 41,46,50 tures were characterized by NMR and HRMS. The HPLC chromatogram presents a single peak for each compound, despite the different conformations observed by NMR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Criteria used in the identification of γand β-turn characteristics. 41,46,50 tures were characterized by NMR and HRMS. The HPLC chromatogram presents a single peak for each compound, despite the different conformations observed by NMR.…”
Section: Resultsmentioning
confidence: 99%
“…31,32 Synthesis of self-assembled peptides utilizing van der Waals forces, hydrogen bonds, hydrophobic and aromatic π-π stacking is another way to form secondary structures, such as turns, helices, and sheets. [33][34][35][36][37][38][39][40] A γ-turn 41 and a β-turn [41][42][43][44][45][46][47][48][49][50] are presented in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…An intriguing example of a fully synthetic turn inducing scaffold comes from Albericio et al (2008), who described the synthesis of a novel trishomocubane amino acid (figure 10) used in the centre of the hexa-alanine polypeptide to generate a (Ala) 3 -cage-(Ala) 3 heptapeptide. Following HPLC purification of diastereomers, structures of the two peptide forms were determined using X-ray crystallography and their structural characteristics were examined.…”
Section: Turn Structuresmentioning
confidence: 99%
“…Previous studies have shown the successful synthesis of a trishomocubane cage peptide with unique β‐turn characteristics using X‐ray analysis 15. In an effort to study the turn inducing effect of the PCU amino acid 1 , the synthesis of the heptapeptide 2 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring the coupling of the first alanine on the amino function of the PCU amino acid 2 sequence (NH 2 ‐PCU‐(Ala) 3 ‐resin) was problematic as a positive result with the ninhydrin test could not be observed, even upon extended reaction times. This was attributed to the steric hindrance exerted by H‐11s on the amino group at C‐8 15. It is known that a relative simple amino acid such as α‐aminoisobutyric acid (AIB) pose considerable steric hinderance for peptide coupling reactions 31, 32.…”
Section: Introductionmentioning
confidence: 99%